Induced Hypothermia in Patients with Septic Shock and Ventilator-demanding Respiratory Failure. (4th October 2017) - Itenov, Theis Skovsgaard; Johansen, Maria Egede; Bestle, Morten; Thormar, Katrin; Hein, Lars; Gyldensted, Louise; Lindhardt, Anne; Christensen, Henrik; Damby, Stine Estrup; Pedersen, Henrik Planck; Harmon, Matthew; Soni, Uday Kant; et al.
Abstract: Background: Animal models of serious infection suggest that 24 hours of induced hypothermia improves circulatory and respiratory characteristics and enhances survival, but whether therapeutic mild hypothermia in such conditions is of clinical benefit remains unknown. We, therefore, tested whether reducing core temperature to 32–34 o C in critically ill patients with septic shock and ventilator-demanding respiratory failure improves survival and reduces organ dysfunction. Methods: In this multi-national trial, patients with septic shock were enrolled within 6 hours of onset of septic shock and ventilator-demanding respiratory failure and randomized 1:1, stratified by site (target sample = 560), to routine thermal management or 24 hours of induced hypothermia (target 32–34°C) followed by 48 hours of normothermia. Other aspects of care were per routine in each participating center. The primary endpoint was 30-day all-cause mortality. Results: At the third ordinary interim analysis, after recruitment of 432 participants, the Data and Safety Monitoring Board recommended the trial be terminated for futility; the conditional power for rejection of the null hypothesis in favor of efficacy was null. In the induced hypothermia group, target temperature was reached within median 3.2 hours [IQR: 2.2, 4.8], and maintained for 24 hours [IQR: 24, 24] (Figure 1). There was no evidence for a difference in 30-day mortality risk in patients randomized to hypothermia (96/217) vs. routine thermal management (77/215): relative risk 1.24 [95% CI: 0.98, 1.56] (Figure 2). At the end of the temperature intervention (72 hours), more patients assigned to hypothermia were in continued shock (vasoactive medication 71% vs. 58%; P = 0.01), and fewer cooled patients had inflammatory control (32% vs. 47% had CRP decline of >30%, P = 0.005). More harm from cooling was seen in patients entering the trial with normal renal function and with normal platelet count (P for interaction < 0.05). Conclusion: Among patients with septic shock and ventilator-demanding respiratory failure, induced hypothermia did not improve survival, but adversely affected the duration of shock, and inflammatory control. Induced hypothermia should not routinely be used in patients with septic shock. Disclosures: All authors: No reported disclosures.